PENGARUH SISTEM PENGUKURAN KINERJA STRATEJIK TERHADAP KINERJA MANAJERIAL (Studi Empirik pada Perusahaan Transportasi di bawah Naungan Kementrian BUMN di Wilayah Jawa) - Winarsih . (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
This study aims to investigate the effect of strategic performance measurement system on managerial performance that isdirectly tested through four variables; job relevant information, role ambiguty, role conflict and role overload. This studyused the perspective of goal setting theory and role theory in explaining inter-variable relationship. Data collected in thissurvey was primary data from 329 functional managers of state-owned transportation companies under the auspices ofMinistry of State Owned Enterprise. Samples were taken using stratified random sampling. Of 329 questionnaires, 264were used in this research with respon rate of 80,55%. Data analysis was conducted using structural equation models inLISREL 8,5. The result of statistictic test indicated that strategic performance measurement system was, but notsignificantly, associated with managerial performance. Further findings indicated that strategic performance measurementsystem was significantly associated with job relevant information, but no association was found with role ambiguity.However, strategic performance measurement system was significantly assosiated with role conflict and role overload.Furthermore, the result of research test indicated that job relevant information was not associated with role ambiguty; roleconflict and role overload, but significantly associated with managerial performance. Based on the result, it can beconferred that role ambiguity was positively related and had a significant impact on managerial performance. In the otherhand, role conflict and role overload are positvely but not significantly assosiated with managerial performance.The resultof the role test of mediating variables has shown that job relevant information, role ambiguity, role conflict and roleoverload significantly mediated the effect of strategic performance measurement system toward managerial performance.Keywords : Strategic Performance Measurement System, Job Relevant Information, Role Stress Characteristic andManagerial Performance